President Rodrigo Duterte on Year 3 - Mendoza, Ronald U (Archīum Ateneo, 2019)
Since his election in 2016, Philippine President Rodrigo Duterte has faced several challenges like the Marawi siege and the continuing Chinese encroachment in the West Philippine Sea. This article examines the major economic and political issues the Duterte administration has dealt with, as well as the accomplishments and failures of the administration in the past three years. It presents a brief analysis of the economic situation in the country and a discussion on the anti-drugs campaign and federalism initiative. The article concludes by expounding on the possible scenarios moving forward, especially on the president’s reform agenda, in light of the results of the 2019 midterm elections.